Did the universe design itself? - Goff, Philip (International journal for philosophy of religion, 2019)
Many philosophers and scientists believe that we need an explanation as to why the laws of physics and the initial conditions of the universe are fine-tuned for life. The standard two options are: theism and the multiverse hypothesis. Both of these theories are extravagant and arguably have false predictions. Drawing on contemporary philosophy of mind, I outline a form of panpsychism that I believe offers a more parsimonious and less problematic explanation of cosmological fine-tuning.